Individual Survival Curves Comparing Subjective and Observed Mortality Risks - Luc Bissonnette; Michael D. Hurd; Pierre-Carl Michaud (Institute for the Study of Labor (IZA), 2014)
In this paper, we compare individual survival curves constructed from objective (actual mortality) and elicited subjective information (probability of survival to a given target age). We develop a methodology to estimate jointly subjective and objective individual-survival curves accounting for rounding on subjective reports of perceived mortality risk. We make use of the long follow-up period in the Health and Retirement Study and the high quality of mortality data to estimate individual survival curves which feature both observed and unobserved heterogeneity. This allows us to compare objective and subjective estimates of remaining life expectancy for various groups, evaluate subjective expectations of joint survival and widowhood by household, and compare objective and subjective mortality with standard life-cycle models of consumption.
Keywords: C81; D84; I10; 330; subjective probabilities; old age mortality; joint survival of couples